Environmental Toxins and Oxidative Stress: The Link to Cardiovascular Diseases - Rasheed O. Sule; Gabriela Del Toro Rivera; Tanishq Vaidya; Emily Gartrell; Aldrin V. Gomes (Antioxidants)
Cardiovascular diseases (CVDs) remain a leading global health concern, responsible for substantial morbidity and mortality. In recent years, as our understanding of the multifaceted nature of CVDs has increased, it has become increasingly evident that traditional risk factors alone do not account for the entirety of cardiovascular morbidity and mortality. Environmental toxins, a heterogeneous group of substances ubiquitous in our surroundings, have now entered the spotlight as offenders in the development and progression of CVDs. Environmental toxins include heavy metals, air pollutants, pesticides, and endocrine-disrupting chemicals, among others. Upon exposure, they can elicit oxidative stress, a condition characterized by an imbalance between the production of reactive oxygen species (ROS) and the body’s ability to detoxify and repair the resulting damage. Oxidative stress triggers a cascade of events, including inflammation, endothelial dysfunction, lipid peroxidation, and vascular remodeling, which can contribute to the development of atherosclerosis, hypertension, and other cardiovascular pathologies. This article delves into the molecular mechanisms underpinning oxidative stress-mediated cardiovascular damage induced by environmental toxins, emphasizing the role of specific toxins in this process. Further research is necessary to understand how individual susceptibility and genotype influence the impact of environmental toxins on oxidative stress and the risk of CVD.